Isolated or integrated? Evaluation of ageing-friendly communities in Old Beijing City based on accessibility, social inclusion and equity. Issue 3 (March 2020) - Wang, Fang; He, Peiwen; Yuan, Congcong; Wang, Shunyi
Due to a rapidly growing ageing population, China is experiencing a rapid urbanisation, resulting in the uneven construction of public facilities. Therefore, the elderly have disproportionate access to public facilities and services. These problems are much more serious in old cities because of a fierce contradiction between society and land use. However, elderly populations are significant to the old city because they are the soul of the old city. Importantly, the old city is a container of memories of their lives as well as an environment they are acquainted with and unwilling to leave. Therefore, whether the urban space in the old city is ageing-friendly and whether the elderly are isolated or integrated in the current urban environment are questions addressed by this study. Based on the World Health Organization's concept of an elderly-friendly city, this study constructed an elderly-friendly urban space evaluation system based on accessibility, social inclusiveness and equity and analysed four types of ageing facilities in 25 blocks of Old Beijing City. The results showed that the ageing resources in Old Beijing City are insufficient and uneven, and revealed that the development of the old city has a positive impact on the construction of an elderly-friendly community.